Two-tier system for remunerating excess reserve holdings - Miguel Boucinha; Lorenzo Burlon; Marco Corsi; Guido Della Valle; Jens Eisenschmidt; Iwona Marmara; Sebastiaan Pool; Julian Schumacher; Olivier Vergote (European Central Bank (ECB), 2022)
This paper reviews the experience of the ECB with the two-tier system for excess reserve remuneration that exempted a portion of banks' excess liquidity (EL) holdings from the negative interest rate of the ECB's deposit facility. The two-tier system aimed to support the bank-based transmission of monetary policy, while preserving the positive effect of the ECB's negative interest rate policy on the accommodative stance of monetary policy. By signalling that the side effects of the negative interest rate policy could be mitigated, the two-tier system supported the ECB's forward guidance on key policy rates. Banks made swift use of the system by filling their allowances through money market transactions, reserves reallocation within their banking groups or by reducing security holdings. Although introducing the system increased turnover of reserves between banks, money market rates remained fully anchored to the deposit facility rate. The system effectively safeguarded the pass-through of monetary policy by providing significant relief to banks from their cost of holding EL and supporting banks' net interest rate margins and net worth. Factoring in the rates at which banks obtain EL shows that the net cost of holding EL for banks in 2021 remained substantially below the levels seen before the exemption was introduced. Ultimately, the system supported the transmission of monetary policy to the real economy, in particular the transmission of negative interest rates to lower lending rates.
Keywords: E41; E43; E52; E58; G11; G12; 330; exemption scheme; two-tier system; excess liquidity; monetary policytransmission; negative interest rates